2016
DOI: 10.1016/j.bbi.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral viral infection induced microglial sensome genes and enhanced microglial cell activity in the hippocampus of neonatal piglets

Abstract: Although poorly understood, early-life infection is predicted to affect brain microglial cells, making them hypersensitive to subsequent stimuli. To investigate this, we assessed gene expression in hippocampal tissue obtained from a previously published study reporting increased microglial cell activity and reduced hippocampal-dependent learning in neonatal piglets infected with porcine reproductive and respiratory syndrome virus (PRRSV), a virus that induces interstitial pneumonia. Infection altered expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…PRRSV infects porcine alveolar macrophages, leading to interstitial pneumonia [39]; the symptoms include anorexia, fever, and sometimes cyanosis [40], similar to what is observed with a human influenza infection [41]. Previous studies in our laboratory have shown that early postnatal PRRSV infection results in reduced neurogenesis and enhanced microglial activity in the neonatal hippocampus [42, 43], and that postnatal PRRSV infection impairs neonatal piglet performance in a hippocampus-dependent learning and memory task [44]. More recent evidence from our porcine MIA model demonstrates that prenatal exposure to maternal PRRSV infection causes altered social behaviors postnatally, while prolonged microglial activation is not evident [45].…”
Section: Introductionmentioning
confidence: 78%
“…PRRSV infects porcine alveolar macrophages, leading to interstitial pneumonia [39]; the symptoms include anorexia, fever, and sometimes cyanosis [40], similar to what is observed with a human influenza infection [41]. Previous studies in our laboratory have shown that early postnatal PRRSV infection results in reduced neurogenesis and enhanced microglial activity in the neonatal hippocampus [42, 43], and that postnatal PRRSV infection impairs neonatal piglet performance in a hippocampus-dependent learning and memory task [44]. More recent evidence from our porcine MIA model demonstrates that prenatal exposure to maternal PRRSV infection causes altered social behaviors postnatally, while prolonged microglial activation is not evident [45].…”
Section: Introductionmentioning
confidence: 78%
“…Rod‐shaped microglia form as early as 1 dpi, peak in the subacute window, and align linearly in the cortex 7 dpi (Taylor, Morganti‐Kossmann, Lifshitz, & Ziebell, ). This structure is observed in other pathological contexts, including aging and chronic viral infection (Bachstetter et al, ; Ji, Schachtschneider, Schook, Walker, & Johnson, ; Sierra et al, ; Yuan, Liang, Peng, Lin, & So, ). Thus, it may represent a conserved response to neuronal degeneration/damage.…”
Section: Introductionmentioning
confidence: 81%
“…Notably, infection at a later stage of development, postnatal day (P)30, does not have the same persistent impact, implicating a critical window [42]. Early-life viral infection of piglets, who demonstrate similar brain growth trajectories and time course as humans, similarly induces a long-term priming effect on microglia [43]. Specifically, microglia collected at P28 from piglets infected with virus at P7, display enhanced phagocytic and migratory activity, increased sensitivity to a second challenge with LPS and Poly I:C, as well as increased soma size compared to controls, closely supporting our findings in rodents [20,44].…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 99%